Papel anticíclico do emprego e renda gerados por micro e pequenas empresas em Sergipe - Silva Júnior, José Jucundo da (2013)
Small companies in Brazil are lodged by Complementary Law No. 123/2006 that classifies them as a maximum limit of annual gross invoicing. That law also provides the simplification in the inflow of federal, state and municipal taxes and reduction of the tax burden through resignation of tributes. Through that law, it is recognized the social role of the small companies, including the potential generator of jobs, especially in crises. In this sense, this thesis discusses the role of small enterprises in the generation of employment and income in Sergipe and, this way, the impact of possible reduction in taxes, with the relief of part of the ICMS, in periods of economic slowdown. For this, are used data available by INSS, which encompass the entire quantitative micro-enterprises of the State. Are also used data supplied by the State Secretary of Finance, concerning the taxpayers of ICMS, the ICMS collected, value added tax and cadastral information. The Laffer Curve is adopted as an auxiliary instrument for checking the increase of economic activity before a tax relief. It was detected the importance of the small enterprises of Sergipe, that are part of the "Simples Nacional", in the generation of employment and income, the countercyclical character of the small enterprises and the evidences that there is room for progress in the reduction of taxes for the same, in order to guarantee the increasing levels of employment and income.